Paradoxes of Stasis : Literature, Politics, and Thought in Francoist Spain - Gajić, Tatjana, 1964- (Book collections on Project MUSE., 2019)
Paradoxes of Stasis examines the literary and intellectual production of the Francoist period by focusing on Spanish writers following the Spanish Civil War: the regime's supporters and its opponents, the victors and the vanquished. 0 Concentrating on the tropes of immobility and movement, Tatjana Gajic analyzes the internal politics of the Francoist regime and concurrent cultural manifestations within a broad theoretical and historical framework in light of the Greek notion of stasis and its contemporary interpretations. In Paradoxes of Stasis, Gajic argues that the combination of Francoism's long duration and the uncertainty surrounding its ending generated an undercurrent of restlessness in the regime's politics and culture. Engaging with a variety of genres-legal treatises, poetry, novels, essays, and memoir-Gajic examines the different responses to the underlying tensions of the Francoist era in the context of the regime's attempts at reform and consolidation and in relation to oppositional writers' critiques of Francoism's endurance.0 By elucidating different manifestations of stasis in the politics, literature, and thought of the Francoist period, Paradoxes of Stasis reveals the contradictions of the era and offers new critical tools for understanding their relevance.